Indigenous research methodologies: decolonizing the Australian sports sciences. (25th October 2018) - Esgin, Tuguy; Hersh, Deborah; Rowley, Kevin; Gilroy, John; Newton, Robert U
Abstract: To design a questionnaire that would determine an Indigenous individual's perceptions of the barriers and motivators to aerobic and anabolic exercise with a series of questions designed to elicit the factors that impact uptake and retention of regular physical activity. For this purpose, a questionnaire was designed to capture information relating to motivators and barriers, traditional physical activities, preferred exercise environments, exercise goals and levels of commitment to physical activity. This article does not report the results of the questionnaire itself but the preparation that was required in order to develop it. Indigenous standpoint theory. Participatory Action Research. A series of consultation meetings were arranged between the first author, a Noongar Aboriginal researcher, with a range of people from the same Noongar community as the author to discuss priorities and develop questions. The drafted questionnaire was shaped with continuous Noongar community feedback to ensure the language, length and appropriateness of questions. Questionnaire reliability was assessed using interclass correlation. Most questions had excellent internal consistency. A consensus was reached on the utility of the questionnaire. The personal contacts of the first author and nature of community involvement in the development of this questionnaire were helpful in assuring that it would be an acceptable tool for the Noongar community. The piloting of the questionnaire was also important in confirming its community acceptability. This article provides a model and suggestions for researching physical activity and exercise in a culturally safe manner.